Crouzon Syndrome: A Case Series of Craniomaxillofacial Distraction Osteogenesis for Functional Rehabilitation - Hariri, Firdaus; Rahman, Zainal Ariff Abdul; Ahmad Bahuri, Nor Faizal; Azmi, M.N.; Abdullah, Norli Anida; Ganesan, Dharmendra (Elsevier, 2018)
Crouzon syndrome (CS) is the most common craniosynostosis syndrome and requires a comprehensive management strategy for the optimization of care and functional rehabilitation. This report presents a case series of 6 pediatric patients diagnosed with CS who were treated with distraction osteogenesis (DO) to treat serious functional issues involving severe orbital proptosis, an obstructed nasopharyngeal airway, and increased intracranial pressure (ICP). Three boy and 3 girls were 8 months to 6 years old at the time of the operation. The mean skeletal advancement was 16.1 mm (range, 10 to 27 mm) with a mean follow-up of 31.7 months (range, 13 to 48 months). Reasonable and successful outcomes were achieved in most patients as evidenced by adequate eye protection, absence of signs and symptoms of increased ICP, and tracheostomy tube decannulation except in 1 patient. Complications were difficult fixation of external stabilizing pins in the distraction device (n = 1) and related to surgery (n = 4). Although DO can be considered very technical and can have potentially serious complications, the technique produces favorable functional and clinical outcomes in treating severe CS. (C) 2017 American Association of Oral and Maxillofacial Surgeons